POTENSI ANTIBAKTERI EKSTRAK BUAH NANAS (ANANAS COMOSUS) DALAM MENGHAMBAT PERTUMBUHAN STAPHYLOCOCCUS AUREUS PENYEBAB KETOMBE - Annisaturrahmah Himawan (LPPM, Akademi Administrasi Rumah Sakit Mataram, 2026)
Dandruff Is A Common Scalp Disorder That May Be Associated With Microbial Growth, Including Staphylococcus Aureus. The Use Of Natural Products As Alternative Treatments Has Gained Increasing Attention, One Of Which Is Pineapple (Ananas Comosus), Which Contains Active Compounds Such As Bromelain, Flavonoids, And Organic Acids With Potential Antibacterial Properties. This Study Aimed To Evaluate The Antibacterial Potential Of Pineapple Fruit Extract In Inhibiting The Growth Of Staphylococcus Aureus. This Research Employed A Laboratory Experimental Design Using The Disc Diffusion Method. Pineapple Extract Was Prepared In Various Concentrations And Tested Against Staphylococcus Aureus. The Results Showed That Pineapple Extract Exhibited Inhibitory Activity Against Bacterial Growth, Indicated By The Formation Of Inhibition Zones Around The Discs. Higher Concentrations Resulted In Larger Inhibition Zones. Therefore, Pineapple Fruit Extract Has Potential As A Natural Antibacterial Agent Against Staphylococcus Aureus.